The Intervertebral Disc Functional Cell Models: a New Revolution for in vitro Toxicology Testing. Issue 1 (April 2016) - Velnar, Tomaz; Bunc, Gorazd; Maver, Uros; Gradisnik, Lidija
Introduction: For diagnostics of discogenic low back pain, local anaesthetics are often used, which may be cytotoxic to intervertebral disc cells. Studies so far have been mainly performed on animal cells. The study aim was to evaluate the effect of local anaesthetics on human intervertebral disc cells in vitro. Material and Methods: Annulus fibrosus and nucleus pulposus cells were isolated from human lumbar intervertebral disc fragments and exposed to various concentrations of lidocaine, bupivacaine and their mixture. Saline solution was used as a control. Three different dilutions (undiluted, 1:2 and 1:4) of anaesthetics were tested. The cells were treated for 6, 24 and 48 hours and examined with for viability. Results: Nulceus pulposus cells were more susceptible than annulus fibrosus cells to the toxic effects of both anaesthetics. Lidocaine was more toxic with the final cell survival fraction of 0%, 10% and 20%. Bupivacaine presented less cytotoxicity with the final survival of 10%, 60% and 80%. Lidocaine-bupivacaine mixture showed an intermediate toxicological effect. Conclusion: Human intervertebral disc cells in vitro are useful for various toxicology tests. They are a valuable model for testing of anesthetic agents. According to the analysis, lidocaine and its mixtures should be avoided due to its high toxicity to the intervertebral disc cells. Bupivacaine was less toxic, especially in 1:4 dilutions and may be recommended for the intradiscal diagnostics.